The effect of plant extracts on cancerous cells and the study of some Indicators - Mater, Haifa Nori; Slman, Zainab Anass; Al-Dulaimi, Sanaa Abed Hammood; Atiyah, Hassan Lafta (Edelweiss Applied Science and Technology, 2024)
The method of treating many plants, including Rheum ribes, is known by many scholars and physicians. In contrast to what chemotherapy costs, the cost of plant treatment is very cheap. The aim of the study is to determine the Cytotoxicity Effect of Ethanolic Rheum ribes Leaf extract Against the HepG2 Cell line. The study used an in vitro assay at varying concentrations for the cytotoxic activity of the extract of Ethanolic Rheum ribes Leaf. The most notable decrease in viable cell count was 62.5, 125 and 250 mg/ml, which seemed to induce cell death induction. The findings showed that leaf ethanol extract at different concentrations affects the HepG2 parameters of cells (Effect of rheum ribes on viability cells, Effect of rheum ribes on Mitochondrial membrane permeability, and Effect of rheum ribes on Cytochrome c). Rheum ribes, the study states, may be treated as a dietary antioxidant and anticancer agent.